Integrative physiology and traditional naturopathic practice: Results of an international observational study - Amie Steel; Joshua Z. Goldenberg; Jason A. Hawrelak; Hope Foley; Sophia Gerontakos; Joanna E. Harnett; Janet Schloss; Rebecca Reid (Integrative Medicine Research)
Background: Naturopathy is one of seven distinct traditional medical systems acknowledged by the World Health Organization. Naturopathic principles and philosophies encourage a focus on multiple body systems during case-taking and the design of treatments. Little is known about whether such teaching translates into practice. This study aimed to characterise naturopathic practice as it relates to the identification of multiple physiological systems in the diagnosis and treatment of patients. Methods: A cross sectional study was conducted in collaboration with the World Naturopathic Federation. A survey capturing clinical diagnostic and treatment considerations for up to 20 consecutive patients was administered to naturopaths in 14 countries. Results: Naturopaths (n = 56) were mostly female (62.5%), aged between 36 and 45 years (37.5%), in practice for 5–10 years (44.6%), and consulting between 11 and 20 patients per week (35.7%). Participants completed the survey for 851 patient cases. Naturopaths reported a greater number of physiological systems relevant to clinical cases where the patients were working age (18–65 years) (IRR 1.3, p = .042), elderly (65 years and over) (IRR 1.4, p = .046), or considered by the naturopath to have a chronic health condition (IRR 1.2, p = .003). The digestive system was weakly associated with patients based on chronicity of the health complaint (V = .1149, p = .004), or having a musculoskeletal complaint (V = .1067, p = .002) autoimmune pathophysiology (V = .1681, p < .001), and considered relevant in respiratory (V = .1042, p = .002), endocrine (V = .1023, p = .003), female reproductive (V = .1009, p = .003), and integumentary (V = .1382, p < .001) systems. Conclusion: Naturopaths across the world adopt an integrative physiological approach to the diagnosis and treatment of chronic and complex health care complaints..